Dearth of information technology governance studies in developing nations: making case for Nigeria - Ajayi, Binyamin Adeniyi; Olanrewaju, Rashidah Funke (2014)
Can Nigeria afford to be oblivion of governance of information technology (IT)? This study explores the dearth of research in the field of Information Technology Governance (ITG) in the developing nation context. It goes to show the reason behind the need to think out of the box which informed the focus on ITG in developed nations. ITG is seen as the desired IT behaviour geared toward sustaining the current and future need of an organisation. The study enumerates how studies on ITG are gaining currency in developing nations such as Malaysia. A search into databases, hosting academic articles, was initiated to investigate the state of ITG endeavour in Nigeria and Malaysia, both commonwealth nations. The draft of the Nigerian ICT Policy 2011 was also studied. What is observed is that while Malaysia is coming up with such reports, same could not be conveniently said of Nigeria. Since the purpose of governance is to ensure symbiotic relation between IT and the business so as to leverage development, developing nations must be ready to give the paradigm a consideration. The need for the executive leaders to be interested in how IT is properly leveraged in public and private organisations is an impetus to nation development. Reporting such will go a long way in popularising the essence of the ITG paradigm.